Using multi criteria decision-making (MCMD) for green supplier selection - Atthirawong, Walailak (My University, 2019)
At present, the level of consciousness and awareness about environmental problems are increasingly internationally concerned from society businesses and governments globally. A number of organizations have begun paying greater attention to diminish the harmful impact of business activities in terms of production, consumption and purchasing behavior which may affect the environment. Despite environmental concern, numerous consumers are willing to pay more for environmental benefits. Supplier selection process is a key role which helps the business to be success in a global arena. The appropriate supplier selection is one of the most important issues for any organization which affecting the total supply chain performance and the quality of final product. Thus, this paper proposes an approach for evaluation and ranking suppliers. In particular, the main focus of this study is to incorporate environmental responsibility requirements into supplier selection. An illustrate example in a cosmetic and beauty community enterprise was conducted to implement how to select the most suitable supplier using TOPSIS method. A set of criteria and sub-criteria were identified from a real case company. The decision was made on the basis of observation of three suppliers with four criteria and ten sub-criteria. The main contribution of this study provides a noteworthy tool to help decision makers in the selection process and reduce the subjective bias to some extent.
Keywords: Environmental concern; Green supplier selection; Multi criteria decision-making (MCMD); One tumbon one product (OTOP) enterprise; Technique for order of preference by similarity to ideal solution (TOPSIS)